Aging Processes of Polyethylene Mulch Films and Preparation of Microplastics with Environmental Characteristics - Wang, Ting; Ma, Yini; Ji, Rong (Bulletin of environmental contamination and toxicology, 2021)
In this study, we explored the aging processes of a commercial polyethylene (PE) mulch film under UV irradiation and compared the laboratory aged films with films aged in nature. Overall, the aged films obtained from laboratory conditions were similar with that from natural conditions. Among the investigated factors, UV irradiation was crucial in the aging of the films, producing cracks and oxygen-containing functional groups on the films surface, constantly with natural aging. The formation of cracks induced a decrease of mechanical strength as well as the formation of MPs on the surface. The chemical oxidations detected by Fourier-transform infrared spectroscopy (FTIR) usually happened after the observed physical changes during aging. Moreover, a protocol was developed for laboratory preparation of MPs with characteristics similar with that from environmental aging and PE MPs with sizes of 2–400 μm could be produced in large amounts at relatively short period of time.